CdS Decorated on Hierarchically Structured Single Crystal TiO2 Nanosheets for Enhanced Photoelectrochemical H2 Generation. Issue 19 (5th October 2022) - Raza, Waseem; Kerketta, Ujjaval; Hwang, Imgon; Schmuki, Patrik
Abstract: Single crystal anatase TiO2 nanosheets (TNS) were grown on a fluorine‐doped tin oxide (FTO) substrate and then modified via multiple TiCl4 treatments to produce a hierarchical TiO2 structure. This high surface area hierarchical structure was then decorated with CdS (as a visible light absorber) using SILAR treatments. The resulting photoanodes provide a greatly enhanced photoelectrochemical H2 generation capability. For the optimized TiO2 and CdS decorated TNS electrode, a photocurrent magnitude of 3.5mA/cm 2 at 0.5V Ag/AgCl (under AM 1.5G, 100mW/cm 2 ) was obtained, and an applied bias to photoconversion efficiency (ABPE) of 2.5% could be reached. The increase in the specific surface was provided by the hierarchical TiO2 structure responsible for the improved performance in comparison to the plain, non‐hierarchical electrode with an ABPE=0.8%. Even after particle decoration, the rapid electron flow through the single‐crystalline scaffold was maintained. Consequently, the photoanode presented here best integrates in a synergistic manner, a larger surface area, a fast electron transport, and effective visible light harvesting properties. Abstract : Optimal performance : Rationally designed CdS sensitized hierarchical TiO2 nanosheets with a high surface area were prepared using a simple hydrothermal method. They demonstrated high photoelectrochemical H2 generation capability, with an applied bias to photoconversion efficiency (ABPE) of 2.5%.